The role of globalization, economic growth and natural resources on the ecological footprint in Thailand: evidence from nonlinear causal estimations - Hussain, Hafezali Iqbal; Haseeb, Muhammad; Kamarudin, Fakarudin; Dacko-Pikiewicz, Zdzisława; Szczepańska-Woszczyna, Katarzyna (MDPI AG, 2021)
The environmental issue has become a global problem that needs to be examined frequently, motivating researchers to investigate it. Thus, the present study has investigated the asymmetric impact of globalization, economic growth and natural resources on the ecological footprint in the presence of environmental Kuznets curve (EKC) in Thailand. The study has used annual time series data from 1970 to 2018. The study applied a novel method of nonlinear autoregressive distributive lag (ARDL). In particular, the current study has investigated the effect of positive and negative shocks on the independent variable on the dependent variable. The findings have confirmed that the effect of globalization and natural resources are significant and nonlinear. However, the effect of negative shocks of globalization and natural resources is more dominant on the ecological footprint in Thailand than the positive shocks of both variables. Moreover, the present study has also tested the presence of EKC in Thailand, and the findings confirm the presence of an inverted U-shape curve in the Thailand economy.